Pengaruh Infrastruktur, Investasi, dan Pertumbuhan Ekonomi Terhadap Kesejahteraan Masyarakat Melalui Kesempatan Kerja - Awandari, Luh Putu Putri; Indrajaya, I Gst Bgs (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 12, Desember 2016 (pp. 1347-1585), 2017)
Infrastructure development is believed to be able to move the real sector, labor intensive boost public and government consumption, as well as trigger the production activities. Economic growth, employment is often associated with investment as the main drivers for creating a prosperous society. Social welfare and employment have a linkage, which describes the role of public employment in achieving development goals, namely the social welfare. This research was conducted in the province of Bali. Object under investigation is the infrastructure, investment, economic growth, employment and social welfare. This study uses secondary data, and then analyzed using path analysis. The test results showed that the infrastructure, investment and economic growth has a positive and significant effect on employment. Infrastructure, economic growth and employment have a significant positive influence on the social welfare, investment does not have a significant effect  to the social welfare. Infrastructure and investments have indirect influence on social welfare, economic growth does not have an indirect effect on the social welfare through employment opportunities in the Province of Bali.
Keywords: Infrastructure; Investment; Economic Growth; Employment; Social Welfare